An adult case with absence of left pulmonary artery and partial anomalous pulmonary venous connection: Case report and literature review. Issue 3 (25th January 2021) - Asadian, Sanaz; Saedi, Sedigheh; Jahanshahi, Bahareh; Hosseini, Leila; Rezaeian, Nahid
Abstract: Unilateral absence of pulmonary artery is a rare congenital disorder that can remain asymptomatic until adulthood. Absence of left pulmonary artery (ALPA) has been reported in one‐third of these patients. We are the first to introduce an adult case of ALPA associated with partial anomalous pulmonary venous connection. Abstract : Unilateral absence of pulmonary artery is a rare congenital disorder that can remain asymptomatic until adulthood. Absence of left pulmonary artery (ALPA) has been reported in one‐third of these patients. We are the first to introduce an adult case of ALPA associated with partial anomalous pulmonary venous connection.